Circular rose window at Mount Mary Basilica - Mumbai Archive Project Team (Jio Institute, 2024)
The third level of Mount Mary Basilica features a circular rose window bearing the inscription anno junilaei 1904—the golden jubilee year of the promulgation of the Dogma of the Immaculate Conception (December 8, 1854). The current basilica was also opened to the public in the same year.